Pelatihan Pengelolaan Perpustakaan Desa Sebagai Media Literasi Informasi Bencana - Saepudin, Encang; Damayani, Ninis Agustini; Rusmana, Agus (Universitas Pahlawan Tuanku Tambusai, 2025)
Village libraries as information centers have an important role in improving the quality of life and helping to solve problems in rural communities. However, there are still many village libraries that are in simple conditions and have limitations in their management, especially in managing library collections and implementing services. The implementation of community service with the theme of village library management training as a medium for disaster information literacy aims to provide knowledge and skills to village library managers about collecting disaster information sources; processing disaster information sources, and disseminating disaster information sources. The method used in implementing community service is Participatory Rural Appraisal (PRA) to conduct social mapping in determining the main problems faced by the target community. While the training implementation methods are lectures, discussions, and practices. The results of implementing community service are by holding discussions with the community in an effort to social map, as well as delivering basic materials on collection development, processing library materials, and library services, participants have knowledge and skills about the process of collecting disaster information sources; processing disaster information sources, and disseminating disaster information sources through various forms of village library services. The conclusion from the implementation of community service is that village library managers are skilled in managing libraries as centers for disaster information sources.